PENGGUNAAN LEMBAR KERJA SISWA (LKS) KOMIK UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN KOLOID DI KELAS XI IPA SMA NEGERI 1 SUNGAI APIT - Hardiyanto '; Roza Linda; Rasmiwetti ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract:The study on the use of LKS comic to improve student achievement on the subject of colloid in class XI IPA SMANegeri 1 Sungai Apit has done. It isa experiment research with pretest-posttest design. The sample consisted of two classes, XI IPA1 as an experiment class and XI IPA2 as a control class, which was randomly selected after tests of normality and homogeneity.Experiment class were treated with the use of LKS comics while not using LKS control class comic. Data analysis technique was used t-test. Based on the results of final processing data use t-test formula obtained tcount>ttable is 3,46>1,67, it means that the applying of question card media can improve student achievement on the subject of colloids in class XI IPA SMA Negeri 1 Sungai Apit. The category improvement of student achievement in experiment class was high category with a score gain normalized is 0,73.Keywords :LKS comics, Learning achievement,and colloid